1997
DOI: 10.1111/j.1601-0825.1997.tb00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of supervised chlorhexidine mouthrinses on untreated gingivitis

Abstract: sumptive therapeutic effect of chlorhexidine digluconate in a population with untreated gingivitis and presence of abundant calculus. SETTING AND STUDY DESIGN: Sixty subjects (ෂ mean Despite the preventive role of chlorhexidine in the devel-CONCLUSION: In conclusion, there was a significant opment of gingivitis, the therapeutic potential of this agent effect of chlorhexidine on gingivitis, although the effect in long-standing, untreated, well-established gingivitis and may be too limited to assure prognostic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Similarly to our study, Brownstein et al [32] have shown that rinsing with CHX without initial prophylaxis in addition to daily plaque control reduce plaque significantly, but gingival index scores insignificantly after 2 months in patients with moderate to severe gingivitis. Corbet et al [6] also investigated the therapeutic effects of CHX mouthrinse on untreated gingivitis. They have observed significant differences between CHX and control groups in gingival bleeding scores after 3 months, while plaque …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to our study, Brownstein et al [32] have shown that rinsing with CHX without initial prophylaxis in addition to daily plaque control reduce plaque significantly, but gingival index scores insignificantly after 2 months in patients with moderate to severe gingivitis. Corbet et al [6] also investigated the therapeutic effects of CHX mouthrinse on untreated gingivitis. They have observed significant differences between CHX and control groups in gingival bleeding scores after 3 months, while plaque …”
Section: Discussionmentioning
confidence: 99%
“…Although there are many products used to control plaque and gingivitis, chlorhexidine digluconate (CHX) has received the greatest attention due to its superior clinical and microbiological effectiveness [5][6][7][8]. It is considered as the gold standard for oral antiseptics [9].…”
Section: Introductionmentioning
confidence: 99%
“…Corbet et al 58 tested the therapeutic effect of 0.12% CHX gluconate, compared to a placebo solution, in individuals with established untreated gingivitis in a parallel‐control group design. The mean GI of the CHX group was reduced significantly from 1.40 to 1.08, with a marked reduction in the percentage of sites with GI = 2 (from 50% to 36%).…”
Section: Discussionmentioning
confidence: 99%
“…The results by Brownstein et al showed that CHX mouthrinse in addition to daily plaque control without initial prophylaxis reduced plaque significantly, but gingival index scores remained unchanged after 2 months in patients with moderate to severe gingivitis [46]. However, Corbet observed no significant differences in plaque index scores in patients with gingivitis while significant difference was found between CHX and control groups in gingival bleeding scores after 3 months [5]. In other study Zanatta et al reported little antiplaque and antigingivitis effect of CHX mouthrinse on previously plaque covered surfaces and pointed out to the importance of removing established biofilm before CHX usage [47].…”
Section: Discussionmentioning
confidence: 99%